(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Idioms serve as vital linguistic elements that summarize the cultural and historical heritage of a society. This study examines the cultural dimensions of English idioms in relation to their Uzbek equivalents, emphasizing how these expressions convey national identity, traditions, and social values. While some idioms share similar meanings across both languages due to universal human experiences, others are deeply rooted in distinct cultural contexts. The research focuses on idioms related to family, food, nature, and emotions, illustrating how language reflects a community’s worldview. Additionally, the study explores challenges in translating idioms between English and Uzbek, highlighting the necessity of cultural awareness for effective cross linguistic communication.